Towards a unique artistic constitution of light: an aesthetic investigation of laser sciences. (2017) - Ahmedien, Diaa Ahmed Mohamed
This article assumed a communicative model and an informative model as two interpretative approaches to classify laser artworks. Hence, it attempted to determine how some artists struggled to build a unique constitution of laser light usage in their own revolutionary artworks and how they managed to conceptualise the scientific aspects behind the laser light and, therefore, emphasised laser art as an independent artistic trend in sciences of visual arts and as a form of advanced light arts in contemporary visual arts. By classifying the use of laser light in the arts qualitatively and quantitatively, this study tried to elucidate how scientific developments in the physics of laser light have seriously affected the essence of the contemporary aesthetics, in which a non-traditional aspect of the relationship between art, sciences and technology can be embodied. In addition, how can the physics of laser light contribute to a fundamentally change in the concept of light as an artistic material and medium in today's art?